(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to encourage students’ utilization of library resources for better academic performance necessitated this study. The study ascertained the benefit of utilization of library resources as perceived by business subjects’ students in secondary schools in Ogidi zone, Anambra State. Descriptive survey research design was adopted for the study. The population consisted of 3577 business subject students and a sample size of 520was drawn for the study using stratified random sampling techniqueOne research question guided the study and two null hypotheses were tested. An 11- item structured questionnaire validated by three experts was used for data collection. The reliability of the instrument was established using test re-test method and data analyzed using Pearson Product Moment Correlation Coefficient; this yielded reliability coefficient of 0.83. Data were analyzed using mean and standard deviation to answer the research question and to determine the closeness of the respondent’s means, while z-test was used to test the null hypotheses at 0.05 level of significance. The results revealed that business subject students in secondary schools in Ogidi zone, Anambra State agreed that library resources help students to use and cite materials accurately. The students strongly agree that library resources offer an environment that is conducive for study. It was found that the business subject students did not differ significantly on their mean responses on the benefit of utilization of library resources in secondary schools based on gender and location of the school libraries. It was recommended among others that management of secondary schools in Anambra State should organize seminars and workshop programs to enlighten student on the relevant and the use of library resources. This will help in enhancing the usage of library resources among students and improve their academic performance.